2016
DOI: 10.1111/mec.13586
|View full text |Cite
|
Sign up to set email alerts
|

Inferences from tip‐calibrated phylogenies: a review and a practical guide

Abstract: Molecular dating of phylogenetic trees is a growing discipline using sequence data to co‐estimate the timing of evolutionary events and rates of molecular evolution. All molecular‐dating methods require converting genetic divergence between sequences into absolute time. Historically, this could only be achieved by associating externally derived dates obtained from fossil or biogeographical evidence to internal nodes of the tree. In some cases, notably for fast‐evolving genomes such as viruses and some bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
129
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 106 publications
(226 reference statements)
4
129
0
Order By: Relevance
“…This clearly indicated that the tip dates were informative and could provide sufficient calibrating information for the analysis (Holt et al. 2012; Rieux and Balloux 2016). The estimated genome wide substitution rate is lower than the estimate for Clostridium difficile (1.88E−7) (He et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This clearly indicated that the tip dates were informative and could provide sufficient calibrating information for the analysis (Holt et al. 2012; Rieux and Balloux 2016). The estimated genome wide substitution rate is lower than the estimate for Clostridium difficile (1.88E−7) (He et al.…”
Section: Resultsmentioning
confidence: 99%
“…Root-to-tip distances were extracted from the ML phylogeny using TreeStat v1.2 (Rambaut 2008). The relationship between root-to-tip distances and tip dates (Rieux and Balloux 2016) was determined using linear regression analysis in R v3.2.0 (R Core Team 2015). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their recent review, Rieux & Balloux () summarize the current state‐of‐the‐art for tip‐dating, and put forward a ‘how‐to’ guide to perform such analyses. While their review is both comprehensive and timely, we feel the need to elaborate on a consequential element of tip‐dating that received only limited attention.…”
mentioning
confidence: 99%
“…While their review is both comprehensive and timely, we feel the need to elaborate on a consequential element of tip‐dating that received only limited attention. Rieux & Balloux () acknowledge that rate estimates from tip‐dated phylogenies may be upwardly biased under less than simple demographic scenarios, such as structured populations (Navascués & Emerson ). One potential explanation put forward for this bias by Navascués & Emerson () is that population structure may produce trees where ancient DNA (aDNA) and modern DNA (mDNA) segregate in different lineages.…”
mentioning
confidence: 99%